Degradation of zopiclone during storage of spiked and authentic whole blood and matching dried blood spots - Jantos, Ricarda; Sabljic, Danica; Skopp, Gisela (International journal of legal medicine, 2013)
Z-drugs such as zopiclone are increasingly involved in forensic cases. Its degradation occurs in solvents and biological fluids. It is assumed that hydrolysis largely accounts for the breakdown of zopiclone in aqueous media. Therefore, a stability study in blood at different storage conditions (−20, 4, 20, and 40°C) was performed to establish changes of the drug’s concentration with time, also including its degradation product 2-amino-5-chloropyridine (ACP). As removal of the aqueous phase may stabilize molecules that are prone to hydrolysis, it was assessed whether the use of dried blood spots (DBS) may be an alternative for storing and analyzing zopiclone and ACP. Spiked and authentic blood samples and corresponding DBS were analyzed using fully validated LC-MS/MS assays. There was agreement between the measurement of zopiclone from either blood or matching DBS in freshly prepared samples. Results showed that zopiclone was unstable in blood at all storage temperatures except at −20°C. Stability of zopiclone in spiked and authentic blood was increased in DBS compared to matching blood samples stored at the same condition. About 85 % of the initial concentration of zopiclone was still intact in DBS on day 8 at 20°C. ACP was formed from zopiclone in equimolar amounts in both media. Therefore, determination of both zopiclone and ACP may be helpful to estimate the initial concentration in both media. Pre-analytical conditions have a major impact on the recovery of zopiclone from blood. With respect to its known advantages, DBS can be recommended as a valuable alternative for the determination of zopiclone from blood.